2001
DOI: 10.1152/ajpregu.2001.281.1.r19
|View full text |Cite
|
Sign up to set email alerts
|

Lactate-transport activity in RBCs of trained and untrained individuals from four racing species

Abstract: In red blood cells (RBC) of horses, both lactate-transport activity and lactate accumulation during races vary interindividually. To study whether similar variation in lactate transport is apparent also in RBCs of other racing species, blood samples were collected from 21 reindeer, 40 horses, 31 humans, and 38 dogs. Total lactate-transport activity was measured at 10 and 30 mM concentrations, and the roles of the monocarboxylate-transporter (MCT) and the inorganic anion-exchange transporter (band-3 protein) we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
33
0

Year Published

2002
2002
2014
2014

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(37 citation statements)
references
References 16 publications
4
33
0
Order By: Relevance
“…Because the levels of thyroid hormones in foals are higher than in mature horses ( 1981), the high MCT activity in the former could be related to high concentrations of thyroid hormones, and the decrease in MCT activity with age could be due to a decrease in the concentration of these hormones. We have earlier concluded that, in horses, training has no effect on lactate transport activity (Väihkönen and Pösö 1998;Väihkönen et al 2001). However, in our earlier study (Väihkönen and Pösö 1998), horses in the different age groups were not the same individuals.…”
Section: Discussionmentioning
confidence: 53%
See 4 more Smart Citations
“…Because the levels of thyroid hormones in foals are higher than in mature horses ( 1981), the high MCT activity in the former could be related to high concentrations of thyroid hormones, and the decrease in MCT activity with age could be due to a decrease in the concentration of these hormones. We have earlier concluded that, in horses, training has no effect on lactate transport activity (Väihkönen and Pösö 1998;Väihkönen et al 2001). However, in our earlier study (Väihkönen and Pösö 1998), horses in the different age groups were not the same individuals.…”
Section: Discussionmentioning
confidence: 53%
“…Of these horses, 43 belonged to the 51 horses also used in the repeatability study. The data from the 15 dams were included in a sedentary control group in our previous study (Väihkönen et al 2001). The repeatability study also includes some horses from which data (one sample from each horse) has been presented in an earlier study (Väihkönen and Pösö 1998).…”
Section: Horsesmentioning
confidence: 99%
See 3 more Smart Citations